Analisa Kebutuhan Luas Minimal Pola Rumah Sederhana Tapak Di Indonesia - Mahatma Sindu Suryo (Jurnal Permukiman, 2017)
The minimum space standard for low cost landed house is 36 m² (SNI 03-1733-2004). The standard refered to the human need for fresh air used for indoor activities. The previous research based on antropometric and human activities in 2011 result in the basic room configuration and minimum space dimension for lowcost landed house. The minimum space dimension based on this previous research is 47.56 m² (11.89m² /person). Compared to the previous study, this research emphasized on space configuration to analysis the minimum space dimension. This paper investigated the minimum space dimension for low cost landed house in Indonesia. This paper simulated the space configuration based on basic room found in previous research to elaborate the most efficient design. The simulation found that the space dimension for low cost landed house is 32,01m²  – 36 m² .